The Effect of Environment and Motivation on Employee Performance with Organizational Culture as an intervening variable on Bank Perkreditan Rakyat Jorong Kampung Tangah Pariaman PT - Wahyuni, Nofi; Heryanto, Heryanto (Archives of Business Research, 2019)
This study aims to find out and analyze: 1) Form of organizational culture, environment, work motivation and employee performance, 2) Environmental influences and motivation on employee performance, 3) Environmental influences and motivation on organizational culture, 4) Effect of work motivation on employee performance , 5) The influence of the environment and motivation on employee performance through organizational culture as an intervening variable. This type of research is a design of causality. The population of this research is all employees at Bank Perkreditan Rakyat Jorong Kampung Tangan Pariaman PT amounting to 42 employees. The data collection technique is a questionnaire. The data analysis technique is path analysis. This study found that: 1) organizational culture, environment, work motivation and employee performance in the scope of Bank Perkreditan Rakyat Jorong Kampung Tangah Pariaman PT in sufficient category, 2) environment and motivation have positive and significant influence on employee performance, 3) environment and have a positive and not significant effect on organizational culture, 4) Work motivation has a positive and significant effect on employee performance, 5) environment and performance have a significant effect on employee performance through organizational culture as an intervening variable